Automation, sustainability, and digitalization at the Port of Callao: an exploration of operations at the South Dock from 2019 to 2022 - Chávez Casimiro, Lesly Graciela (2025)
This research aims to ascertain the impact of automation and sustainability on operations and the implications of digitalization at the South Dock of the DP World Port of Callao between 2019 and 2022. A two-stage mixed structure methodology with a data envelopment analysis (DEA) model is used to assess the relative efficiency of the decision-making units, while a Tobit regression is employed to compare coefficients to determine the significance of the variables. The results provided a comprehensive insight into the dock's performance, showing that digitalization significantly affected supply chain efficiency and. However, the study also highlighted the importance of addressing challenges related to workers' adaptation to new technologies and effective coordination between different actors involved in managing the port supply chain. Collectively, these results offer a deeper understanding of the beneficial influence of digitalization on port operations, highlighting the significance of policies that promote a smooth transition to digital technology in developing nations like Peru.